Effect of Moldboard types, Two depths of Tillage and Two speeds of Tractor in some Physical Properties and Pulverization of Soil - Ahmed Abd Ali. Hamid; Abdul Rahman A. Alsabbagh (Kufa Journal for Agricultural Sciences)
Factorial experiment under randomized complete block design with three replication was conducted in field in collage of Agricultural Engineering Science – University of Baghdad in 2022, for study effect of two types of moldboard slatted and general purpose in some physical properties under two depths of tillage 15 and 25 cm and two speeds of tractor 4.146 and 7.224 km/hr. Slatted moldboard recorded least (best) number of clods > 10 cm 4.58 clod/m2, soil bulk density 1.259 g/cm3, higher porosity 52.48 % and higher volume of disturbed soil 804.14 m3/h. Depth of tillage 25 cm got higher volume of disturbed soil 967.21 m3/h. Depth 15 cm got lower number of clods > 10 cm 4.91 clod/m2, 1.209 g/cm3 and higher porosity 54.35 %. Speed of tractor 7.224 km/h got higher volume of disturbed soil 983.79 m3/ h and least number of clods > 10 cm 7.50 clod/m2. Speed of tractor 4.146 km/h got least bulk density 1.259 g/cm3 and best porosity 52.48 %. No significant interaction speed tractor with moldboard types in bulk density and porosity. The rest of all interactions were significant.